Exchange rate undervaluation, financial development and growth - Sekkat, Khalid (Cairo Economic Research Forum (ERF), 2012)
This paper examines the interaction between financial development and the impact of undervaluation on growth. No evidence is found of a positive effect of undervaluation on growth even with a well-developed financial sector. This conclusion survives different robustness tests such as alternative indicators on financial development, delay in the effect of undervaluation and alternative non-linear assumptions.
Bibliography: p. 15-17
Keywords: Financial economics; EXCHANGE RATE; MONEY; DEVALUATION; CURRENCY INSTABILITY; ECONOMIC DEVELOPMENT